Integration of Activities in the natural environment as contents of education trhough collaborative action-research - Roberto Guillén Correas; Carlos Peñarrubia Lozano (FEADEF, 2013)
The different values †given to Activities in the Natural Environment have become a mandated content block within the area of Physical Education. This research is based on the urging of its practical development of a school in the city of Zaragoza. So far, the analysis of these practices in this school, refers to some specific experiences focused on the volunteer activities done during the «snow week», which means less participant students. Collaborative action-research is the methodology used for this purpose, therefore team-work is demanded to overcome the limitations presented by this block of contents: teacher training as well as both facilities and materials must be provided. Thus, we found two groups of conclusions: firstly, the factors necessary to establish a dynamic collaborative work among teachers of this school. Secondly, the aspects required to design and strengthen the proposed contents of environmental Activities in the school, adapting them to its own physical contextual characteristics